2020
DOI: 10.1177/2158244020914394
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Utilization of Maternal Reproductive Health Care Services in Urban Bangladesh: A Population-Based Study

Abstract: This study examined inequalities in the utilization of maternal reproductive health care services in urban Bangladesh. Data of 6,617 urban women were extracted from most recent two rounds of Bangladesh Demographic and Health Survey, conducted in the years 2011 and 2014. Inequalities in the utilization of antenatal checkup, receiving care from a skilled birth attendant, delivery in health care facilities, and postnatal care were investigated through concentration index. Contributions of selected predictors to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…For instance, the patriarchal system in Bangladesh often restricts women’s decision-making capability and the economic affordability of visiting healthcare facilities. Besides, cultural norms within Islam (the religion of more than 90% of the total population in Bangladesh) do not permit women to leave their homes while pregnant, with pregnant women believed to be highly vulnerable to evil spirits (one reason why their mobility is restricted, particularly during delivery and soon after childbirth) [ 68 ]. These practices are even more prevalent among women with disadvantaged individual-, household-, and community-level characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the patriarchal system in Bangladesh often restricts women’s decision-making capability and the economic affordability of visiting healthcare facilities. Besides, cultural norms within Islam (the religion of more than 90% of the total population in Bangladesh) do not permit women to leave their homes while pregnant, with pregnant women believed to be highly vulnerable to evil spirits (one reason why their mobility is restricted, particularly during delivery and soon after childbirth) [ 68 ]. These practices are even more prevalent among women with disadvantaged individual-, household-, and community-level characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that these factors are the signi cant predictors of SBI in the SBI hot spots area in the Sylhet division. A possible reason for such association is that couples with these characteristics are less likely to access maternal healthcare services, including intrapartum, birthing, and post-partum care [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Providing integrated reproductive healthcare services may help improve the current service delivery. Also, tailoring service modality considering the divisional level barriers is needed 36 , as it is not possible in the current uniform top-down policy approach 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…division), residence and sociodemographic groups; the role of individual determinants (e.g., age and birth order) has less influential after 2015. 27,28 The persistent efforts of the government in integrating community needs into the safe motherhood programs, identifying local needs through community-based platforms and mainstreaming NGOs into community health, are worth acknowledging here as success factors. 27 The study found two exceptions to the above findings.…”
Section: Discussionmentioning
confidence: 99%